200 Laparoscopy versus laparotomy for the management of early stage cervical cancer. Hospital dr sotero del rio. Chile. (18th September 2019) - Puga, O; Perez, MV; Saez, N; Jensen, R; Retamales, J
Abstract : Objectives: The treatment of early stage cervical cancer (IA2 to IIA) is chirurgical, radical hysterectomy with bilateral pelvic lymphadenectomy is the standard recommendation. Our aim is to compare the feasibility, safety and surgical outcomes between laparoscopic surgery (LHR) and open laparotomy (HR) in early stage cervical cancer. Methods: We performed a retrospective review of patients with early stage cervical cancer treated with radical hysterectomy and pelvic lymphadenctomy between 2013 and 2018 Hospital Dr Sótero del Rio, Santiago de Chile. We analyzed clinicals reports and statistical studies was performed. Results: We analyzed 72 patients, 47 (65%) by laparoscopy and 25 (35%) laparatomy. FIGO stage included IA2 (4), IB1(62), IB2 (3), II A (3) Both groups were similars; age, associated pathology, histology (squamus 70%, adenocarcinma 29%, adenoescamoso 1%) and surgical stage. Two patients required conversion to laparotomy. There were no statistical differences between body mass index, pelvic lymph nodes removed (17 vs 16), operative time and adyuvant chemoradiation 28 (39%). LHR need less analgesic and the recovery were faster than laparotomy. The mean estimated lost blood was decreased in the laparoscopic group (145 vs 391 ml), ( p=0, 025 ) and the length of postoperative hospital stay (p =0, 009) were significantly shorter in the LHR .There were two uretheral injuries in both groups one rectum injury in LHR, three wounds infections and obturador nerve section in HR Conclusions: Laparascopic radical surgery has similar therapeutic efficacy compare to HR, however it has more favorable surgical outcomes including less estimated blood loss, faster recovery and shorter hospital stay. Oncologic outcome requires longer follow up.